Designing Research-Based Teacher-Appraisal Forms: A Case of Effective EAP Lecturers in Uzbekistan - Arfa-Kaboodvand, Mandana; Akbarova, Saida (International Journal of Language Education, 2023)
The main aim of this article is to introduce the steps followed in designing effective teacher-appraisal forms to be completed by the students, and teacher-self-reflection forms to be completed by the teachers. After explaining the steps and the reasons behind taking them, we will report on the findings of the study we have conducted following the same procedures to design the forms. The findings have identified the characteristics of effective EAP lecturers according to the 196 students who participated in the study. for EAP lecturers have also provided their input about the characteristics of effective EAP teachers. The collected data suggest the students seem not to differentiate between the competencies required for teaching and learning general English and EAP. The students considered communicative competence the most essential asset of their EAP lecturers. Accurate interpretation of the data emerging from the ratings is another issue addressed in this article. This can guide the teachers to make better decisions.